2018
DOI: 10.1080/0145935x.2018.1491302
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes for children who care for a parent with a severe illness or substance abuse

Abstract: Ketil (2018) Outcomes for children who care for a parent with a severe illness or substance abuse. Child and Youth Services, 39 (4). pp. 228-249.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 67 publications
3
30
0
Order By: Relevance
“…In the present study, students who confirmed caregiving responsibility had more negative health outcomes compared to non-caregiving students. Whereas previous studies have found that young carers experience the caring responsibility as rewarding (Chikhradze et al, 2017), carers in different age groups also report adverse effects (Pakenham et al, 2006;Berglund et al, 2015;Pakenham and Cox, 2015;Greene et al, 2017;Kallander et al, 2018). In line with increased rate of health problems found among carers in general (Koyanagi et al, 2018), the negative outcomes among YACs in the present study were evident on several health markers, i.e., anxiety and depressive symptoms, sleep problems, and somatic symptoms.…”
Section: Negative Health Outcomes and Amount Of Care Responsibilitiessupporting
confidence: 57%
See 1 more Smart Citation
“…In the present study, students who confirmed caregiving responsibility had more negative health outcomes compared to non-caregiving students. Whereas previous studies have found that young carers experience the caring responsibility as rewarding (Chikhradze et al, 2017), carers in different age groups also report adverse effects (Pakenham et al, 2006;Berglund et al, 2015;Pakenham and Cox, 2015;Greene et al, 2017;Kallander et al, 2018). In line with increased rate of health problems found among carers in general (Koyanagi et al, 2018), the negative outcomes among YACs in the present study were evident on several health markers, i.e., anxiety and depressive symptoms, sleep problems, and somatic symptoms.…”
Section: Negative Health Outcomes and Amount Of Care Responsibilitiessupporting
confidence: 57%
“…Having care responsibility may contribute to the development of practical and emotional skills, and is considered to stimulate resilience, problem-solving, empathy, sensitivity and ability to cope with life-challenges (Becker and Becker, 2008). However, research with children, teenagers and older adults with care responsibilities, has shown that there may also be negative outcomes on the mental and physical health of carers (Nagl-Cupal et al, 2014;Berglund et al, 2015;Van Loon et al, 2017;Kallander et al, 2018). Besides a few studies on health outcomes for YACs, we have limited knowledge about the impact of care responsibilities in this life phase.…”
Section: Introductionmentioning
confidence: 99%
“…26,27 Similar to international trends, there has been an increased focus on the needs of children with parents with mental health problems. [12][13][14][15][16][17][18] Consequently, in 2010, Norway added two legislative provisions that oblige health personnel to attend to minor relatives and to designate children-responsible staff (CRS). 28,29 The responsibilities of CRS are to promote and coordinate health personnel's follow-up with patients' minor children.…”
Section: Study Contextmentioning
confidence: 99%
“…5,11 Studies have clearly shown that the children of parents with serious mental health problems face many developmental, emotional, behavioural and educational challenges and are at risk of developing mental health problems themselves. [12][13][14][15][16] Therefore, health personnel should ascertain what kind of support measures these children need and start the necessary followup. [17][18] In Norway, about 15-20% of all hospitalised patients are involuntarily admitted (about 5000 adults).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation